In situ synthesis of SiC reinforced MMC surface on AISI 304 stainless steel by TIG surface alloying - Buytoz, S; Ulutan, M (Elsevier Science Sa, 2006)
In this study, an austenitic stainless steel surface was coated with different silicon carbide powder contents. The process parameters were changed in order to determine their influence on the coating microstructure. The results showed that the silicon carbide particles are completely dissolved during the production. At the lower powder contents, the microstructures consisted of dendrites. However, M7C3 primary carbides were generated at the high powder contents. The hardness of the dendritic structure is in the range 550 HV and 750 HV. However, the hardness of the hypereutectic structures is in the range 890 HV and 1210 HV The lower hardness of dendritic microstructure was related to the presence of primary dendrites and relatively low concentrations of Fe, Cr, Si and C. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: M7C3 carbides; hardfacing; dendritic solidification